Referrals for physical therapy for osteoarthritis during the COVID-19 pandemic: A retrospective analysis - Manmeet Kaur (Public Library of Science (PLoS), 2021)
Background Osteoarthritis (OA) is a leading cause of musculoskeletal pain and disability among Americans. Physical therapy (PT) is recommended per the 2019 ACR /Arthritis Foundation Guideline for Treatment of OA of the Hand, Hip, and Knee. During COVID-19, access to healthcare has been altered in a variety of clinical settings, with the pandemic creating delays in healthcare, with an unknown impact on access to PT care for OA. Objectives We sought to determine whether referrals to PT for OA were reduced in 2020 during the COVID-19 pandemic compared to 2019. Methods A retrospective analysis was done of 3586 PT referrals placed by the University of California, Davis for 206 OA ICD-10 codes from January to November 2019 and from January to November 2020. The numbers of PT referrals per month of each year were compared using both descriptive statistics and Poisson Regression analysis. Results A total of 1972 PT referrals for OA were placed from January to November 2019. Only 1614 referrals for OA were placed from January to November 2020, representing a significant decrease (p = 0.001). Month-by-month analysis of 2020 compared to 2019 revealed statistically significant drops in PT referrals for OA in April (p = 0.001), May (p = 0.001), and August (p = 0.001). Conclusions These findings reveal a significant reduction in the number of referrals for PT for OA placed in 2020 during the first year of the COVID-19 pandemic. These reductions were particularly evident in the months following state-mandated actions and closures. Factors associated with this outcome may include decreased access to primary care providers, perceptions of PT availability by health care providers, decreased mobility limiting access to both clinic and PT appointments, and/or willingness to engage in PT by patients during the pandemic.